Wound-healing effect of honey gel and film - Febriyenti Febriyenti; Henny Lucida; Almahdy Almahdy; Istianah Alfikriyah; Muhammad Hanif (Wolters Kluwer Medknow Publications, 2019)
Background: Honey has been formulated into gel and film dosage forms for burn wound as previously reported. Aims: In this study, we evaluated the ability of honey gel and film to promote the healing of burns and incision wounds on the skin of Sprague-Dawley female white rats. Materials and Methods: Twenty-four female rats were divided into four groups, which were treatment groups (for honey gel or film), negative control, and positive control (treated with marketed product "B"), respectively. Burn and incision wound were created by the method previously reported with slight modification. Parameters such as the percentage of wound closure and the tensile strength of the incision wound were determined. Results: The experimental results showed that honey film has a greater effectiveness to accelerate the healing for burns and incision wound in comparison to the negative control. Conclusions: Two-way analysis of variance indicates the type of treatment group, and time has a significant effect on the burn wound (P < 0.05). Honey film shows the significant difference (P < 0.05) with other group on the incision wound.